2022
DOI: 10.1111/rec.13698
|View full text |Cite
|
Sign up to set email alerts
|

Mulch more so than compost improves soil health to reestablish vegetation in a semiarid rangeland

Abstract: Up to half of the world's drylands have degraded, dysfunctional soils that lower success rates of restoration efforts to reestablish lost vegetation. Because soil amendments of organic matter have the potential to improve multiple ecosystem functions and overall soil health, we added a mulch of whole mesquite (Prosopis velutina) branches—both alone and in combination with 3 and 6 cm of compost—to a degraded semiarid rangeland. We then measured effects of these organic amendments on a suite of soil health indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Our experimental design allowed us to separate the influence of the two different amendment types and demonstrated that it was the combination of cooler temperatures, higher moisture availability and increased nutrients that resulted in the highest plant production. Actually, there was also a very similar study demonstrated that woody branch shelter combined with a thin layer of compost can improve success rates of revegetation in dryland ecosystems by moderating the soil microclimate (such as improving soil moisture and enhancing soil nutrients) (Leger et al, 2022). In this study, the RDA model also showed that plant growth was significantly influenced by all tested indices including soil water, soil organic carbon, Total N, Total P, Available N, and Available P during whole period.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our experimental design allowed us to separate the influence of the two different amendment types and demonstrated that it was the combination of cooler temperatures, higher moisture availability and increased nutrients that resulted in the highest plant production. Actually, there was also a very similar study demonstrated that woody branch shelter combined with a thin layer of compost can improve success rates of revegetation in dryland ecosystems by moderating the soil microclimate (such as improving soil moisture and enhancing soil nutrients) (Leger et al, 2022). In this study, the RDA model also showed that plant growth was significantly influenced by all tested indices including soil water, soil organic carbon, Total N, Total P, Available N, and Available P during whole period.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research has shown that piling branches over the soil can shade and cool the soil yet allow seed germination and plant growth (Li et al, 2018(Li et al, , 2019Leger et al, 2022). And unlike wood chip mulch, the sturdier longer branches facilitate the formation of a loose three-dimensional structure of material above the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the role of mulch under a seeding scenario, in particular where it occurs on highly modified agronomic settings where little natural surface litter remains, focuses not on weed suppression, but on its potential to facilitate seedling emergence and survival by retaining soil moisture, restricting soil temperature extremes (i.e. at shallow depths), and by mediating often harsh soil surface micro-conditions for plants (Cochran 1969;Facelli & Pickett 1991;Bulmer et al 2007;Leger et al 2022). This, of course, requires that weeds are controlled by other means (Coor 2003;Robinson 2015;Humphries et al 2021), which in this study was tested by linked factorial treatments of topsoil removal and 12month herbicide application.…”
Section: Discussionmentioning
confidence: 99%
“…However, in restoration, achieving reliable seed germination and seedling establishment is often difficult because both are highly affected by weed competition (Humphries et al 2021) and environmental extremes (Cole & Lunt 2005;Fenner & Thompson 2005;Read et al 2005). For this reason, surface mulches of various types have been used by practitioners to mitigate these negative effects (Schuman et al 1998;Rokich et al 2002;Cole & Lunt 2005;Read et al 2005;Navarro-Pedre ño et al 2017;Leger et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation